Vibration analysis of continuous microbeams carrying a moving load - Nam, Pham Vu; An Ninh, Vu Thi; Kien, Nguyen Dinh (Vietnam Journal of Science and Technology, 2025)
Vibration analysis of continuous microbeams carrying a moving load is presented in the framework of the Euler-Bernoulli beam theory and the modified couple stress theory (MCST) for the first time. The continuous beams consist of three spans with nonuniform cross-section and simply supported ends. A finite element formulation is derived and used to establish the discretized equation of motion for the microbeams. Natural frequencies and dynamic response are determined with the aid of an implicit Newmark method. The derived formulation is validated by comparing the obtained results with data available in the literature. The numerical investigation reveals the importance of the microstructural size effect on the vibration of the continuous microbeams, and incorporating the material length scale parameter in the formulation leads to an increase in the vibration frequencies, but a decrease of the dynamic response. The effects of the material length scale parameter and moving load velocity on the vibration behavior of the continuous microbeams are studied in detail and highlighted.